2015
DOI: 10.1002/ccd.26264
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement for native aortic valve regurgitation as a bridge to liver transplantation

Abstract: Coexistence of end-stage liver disease (ESLD) and severe valvular heart disease conveyed substantial risk for patients, oftentimes leading to exclusion from liver transplantation candidacy due to inability to safely offer cardiac surgery prior to transplantation. Several approaches have been described, including performing transplantation and valve surgery concurrently, or in sequence. Both options, however, have associated complications: catastrophic repercussion of peri-operative coagulopathy and organ dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[8][9][10][11] History of cirrhosis or liver disease is frequently an exclusion criterion for randomized controlled trials and only a few observations have shown so far the feasibility of TAVR as a bridge or salvage therapy for patients with end-stage liver diseases (n = 6) or before kidney transplantation (n = 1). [12][13][14][15][16] We report herein 3 additional cases of cirrhotic patients with severe AS who benefited from a TAVR procedure while awaiting LT.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] History of cirrhosis or liver disease is frequently an exclusion criterion for randomized controlled trials and only a few observations have shown so far the feasibility of TAVR as a bridge or salvage therapy for patients with end-stage liver diseases (n = 6) or before kidney transplantation (n = 1). [12][13][14][15][16] We report herein 3 additional cases of cirrhotic patients with severe AS who benefited from a TAVR procedure while awaiting LT.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports or series have been published to share the successful and promising experiences of TAVI in the patients awaiting liver transplantation. [26,27] However, the case number was still very small and further investigation should be performed to validate the safety and efficacy of TAVI in this group of patients.…”
Section: Analysis Of the Pooled Resultsmentioning
confidence: 99%
“…There are 2 reports in the literature on patients undergoing transcatheter procedures before LT. Coverstone et al [ 7 ] described 4 patients who underwent aortic balloon valvuloplasty for severe aortic stenosis pre-LT, while Cabasa et al [ 8 ] reported transcatheter aortic valve implantation (TAVI) in another patient with aortic regurgitation listed for LT (Table 1 ). To the best of our knowledge, our patient is the first to undergo an open surgical procedure involving the ascending aorta and the aortic valve prior to LT. We also considered various possible alternative procedures, all of which were discarded.…”
Section: Discussionmentioning
confidence: 99%